Nematicidal Activity of Various Aqueous Extracts against Root-Knot Nematodes (Meloidogyne chitwoodi) - Ece Börteçine Kasapoğlu Uludamar (Journal of Agricultural Sciences)
In this study, the effects of twelve aqueous extracts on the hatching and mortality of second-stage juveniles (J2s) of Meloidogyne chitwoodi were evaluated under in vitro and growth chamber conditions in 2020-2021. The mortality of the J2s increased with the increasing exposure time and concentration for all extracts. Maximum mortality was observed in 50% of all aqueous extracts. Up to 100% maximum mortality was observed in 10% of extracts of Anethum graveolens (100%), Eruca sativa (100%), Ficus carica (100%), Juglans regia (100%), Melia azedarach (100%), Mentha piperita (100%), Vitex agnus-castus (98%), Asphodelus aestivus (96.4%), Eucalyptus camaldulensis (95.6%) after 24 hours and minimum mortality was found in 1% of extracts of Laurus nobilis (6.6%) after 6 hours. Moreover, maximum suppression of hatching was found at 64.2%, 61.0%, and 59.4% with extract of A. aestivus, Nerium oleander, and V. agnus-castus after 7 days, respectively. The pot experiments showed that the gall index was the lowest in soils treated with Ficus carica, Nerium oleander, Laurus nobilis, Eucalyptus camaldulensis and Zingiber officinale extracts. The chemical composition of five aqueous extracts was analysed using gas chromatography-mass spectrometry (GC-MS), and the main components of five aqueous extracts were identified as eucalyptol, 2-methoxy-6,10-dimethyl-dodeca-2E,6Z,10Z-trienoic acid, 12-acetoxy-, dihydroedulan II and α-Zingiberene. The study confirms the potential of mainly L. nobilis, E. camaldulensis, F. carica, Z. officinale and N. oleander extracts for the formulation of new products for controlling M. chitwoodi